2015
DOI: 10.5860/crl.76.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Sustaining the Impact of Less Commonly Taught Language Collections in a Research Library

Abstract: To evaluate the current state of resource sharing and cooperative collection development, this paper examines the relationship between less commonly taught language collections (LCTL) and ILL services. The study examined multiple years of the University of Illinois at Urbana-Champaign’s resource-sharing data. This paper provides a historical narrative for the multilingual collections, collection development strategies, reference services, and outreach initiatives that reinforce and strengthen scholarly communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…While the higher education internationalization literature does not often mention libraries, there is a significant body of library literature that demonstrates the wide range of internationalization activities that academic libraries have engaged in for some time, such as: contributing to general internationalization efforts (Becker, 2006a, 2006b; Bordonaro, 2013; Dewey, 2010), supporting study abroad (Denda, 2013; Kutner, 2009), developing internationally focused and foreign language collections (Hazen and Spohrer, 2007; Lenkart et al, 2015), conducting information literacy activities (Hughes, 2013; Johnston et al, 2014), participating in staff exchanges (Johnson et al, 2010; Somerville et al, 2015), supporting international branch campuses (Green, 2011), and of course, supporting international students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the higher education internationalization literature does not often mention libraries, there is a significant body of library literature that demonstrates the wide range of internationalization activities that academic libraries have engaged in for some time, such as: contributing to general internationalization efforts (Becker, 2006a, 2006b; Bordonaro, 2013; Dewey, 2010), supporting study abroad (Denda, 2013; Kutner, 2009), developing internationally focused and foreign language collections (Hazen and Spohrer, 2007; Lenkart et al, 2015), conducting information literacy activities (Hughes, 2013; Johnston et al, 2014), participating in staff exchanges (Johnson et al, 2010; Somerville et al, 2015), supporting international branch campuses (Green, 2011), and of course, supporting international students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper continues the authors' work published in College & Research Libraries. 5 In both the previous and present study, the authors analyzed five years of ILL lending data, focusing on successful fulfillment of requests for area studies materials received from other institutions. While the previous study identified area studies materials based on language by looking at ILL requests for materials published in languages other than the more commonly taught English, Spanish, French, and German, this study is more expansive.…”
mentioning
confidence: 99%